(untitled) (Research, Society and Development, 2021)
Objective: To evaluate the movements in premature newborns hospitalized in a neonatal intermediate care unit, according to the General Movements Assessment (GMA). Methods: This is a descriptive, exploratory study with a quantitative approach and cross-sectional design, conducted in a Maternal and Infant Hospital in the interior of Bahia, from July to September 2021, consisting of a sample of 20 preterm newborns. The instruments used for data collection of the research were: form from the medical record of the preterm newborns and the GMA scale. Results: The study population presented corrected gestational age between 33 and 39 weeks corresponding to the Writhing Movements phase, it was possible to identify that 65% presented abnormal movement, being 55% predictive for spastic cerebral palsy. Conclusion: The professional physiotherapist, besides performing neurosensory-motor intervention in newborns at high risk for infant development, performs an evaluation in order to detect clinical signs of motor development delays. Every intervention is intended to adjust muscle tone, reduce pain, stimulate muscle synergies and facilitate neurosensory-motor development, it was realized in the study that the GMA assessment instrument, is a reliable facilitator, since very early gestational ages.